Penerapan Metode Daring Sebagai Optimalisasi Media Pembelajaran Bahasa Inggris Masyarakat Milenial Di Masa Pandemi Covid-19 - Hilda - Hastuti; Puspita - Dewi; Riyana Rizki Yuliatin; Abdul - Muhid; Erwin - Suhendra; Wiya - Suktiningsih (Society : Jurnal Pengabdian Masyarakat, 2022)
The level of awareness about education in general and the ability to speak English is still low, especially in the millennial community, so it is necessary to make innovations in learning English. In order to support the implementation of English language learning in millennial communities during the COVID-19, it is necessary to apply an online method. During the pandemic, the government's efforts, one of which is face-to-face learning, cannot be done because it is to reduce and prevent the spread of COVID-19. Based on this explanation, our team held a devotion activity by the title "Implementation of Online Methods as Optimizing English Learning for Millennials in the COVID-19 Pandemic". The results of these activities ran well. It is hoped that this activity can improve the language skills of the millennial community by being much practice, especially English.